Analysis of serum levels of HIF-1α and IL-6 in patients with acute stanford type a aortic dissection - Zheyuan Wang; Junyi Wen; Shaoqin Chen; Lin Lu (Journal of Cardiothoracic Surgery)
Abstract Background Studies have reported that Acute Stanford type A aortic dissection (ATAAD) is associated with hypoxia and inflammation. This study aims to explore the levels of HIF-1α and IL-6 in the serum of patients with ATAAD, and to analyze the association between these two factors as well as their potential clinical significance. Methods Serum samples were collected from 82 ATAAD patients and 19 healthy controls. Subsequently, the levels of HIF-1α and IL-6 in the serum of these samples were measured using the enzyme-linked immunosorbent assay (ELISA). Results The results showed that the serum HIF-1α level in patients with ATAAD were significantly reduced compared with the healthy control group [10.72 (7.28,14.92) vs. 19.54 ± 8.07 pg/mL, p < 0.0001], and the serum IL-6 level were significantly increased [3.12 (1.97, 9.13) vs. 1.13 (0.98, 1.42) pg/mL, p < 0.0001]. Moreover, there was no statistical difference of HIF-1α level in ATAAD patients with or without hypoxemia and IL-6. However, there was a significant positive correlation between the levels of IL-6 and the expression of HIF-1α (r = 0.5435, P < 0.0001). Conclusion We found that levels of HIF-1α and IL-6 were abnormal in patients with ATAAD. Moreover, the HIF-1α and IL-6 level in ATAAD patients were positively correlated, suggesting that HIF-1α and IL-6 may play roles simultaneously during the development of acute aortic dissection.